Benefit of PFO Closure in Cryptogenic Stroke Remains Elusive - Buckley, Rita; Rizzo, Toni (MD Conference Express, 2012)
Approximately 30% to 40% of ischemic strokes are classified as cryptogenic because a recognized cause is not identified [Sacco RL et al. Ann Neurol 1989]. Paradoxical embolism due to patent foramen ovale (PFO) is a possible cause of ischemic stroke, particularly in young cryptogenic stroke patients. Several presentations at TCT 2012 added important data to the growing literature about PFO closure and highlighted how elusive secondary stroke prevention with device therapy remains.